The Impact of Brand Personality on Brand Preference: A Study on Personal Care Products - Sumudu Namali Munasinghe (International Review of Management and Marketing, 2018)
The three factors in the marketing communication context namely, the spokesperson, message and channel is vital in affecting the purchase intention of a consumer. In the Sri Lankan context, the marketers of the personal care brands had put more effort on selecting the spokesperson the most while the consumers tend to give prominence to the message in determining their purchases. Brand personification has become one of the most salient aspect used in the marketing communication context in designing the message. Reflecting a human like character in the brand aims to attract the consumers in a unique manner with the brands. This becomes more vital in the case of brands to which the consumers are personally attached to. Hence, the personification alone wouldn't be sufficient as the means of personifying and the most suitable aspect to be personified in the brand is also vital. This research focused upon understanding the association between brand personality and brand preference, was conducted as a combination of both quantitative and qualitative approaches. The survey with a self-administered questionnaire developed by the researcher, served as the main source of data collection a convenient-judgmental sample. Findings would aid the decision makers in the chosen area of business. Keywords: Brand Personification, marketing communication, brand preference